(untitled) (International Journal of Biology and Chemistry, 2019)
There are some reports for the preparation of several drugs as COX-inhibitors; however, some reagents used in the preparation are expensive and difficult to handle. The aim of this study was to synthesize a steroid-oxazolone derivative using some reactions such as i) hydroxylation-amiination; ii) amidation; iii) alkynyl-addition; iv) aldolization and iv) imination. In addition, a theoretical assessment was carried out to evaluate the interaction of both COX-1 and COX-2 with the steroid-oxazolone derivative using indomethacin and rofecoxib as controls in a docking model. The structure of the compounds obtained was confirmed through elemental analysis, spectroscopy and spectrometry data. The results showed that the steroid-oxazolone derivative has a higher affinity for COX 1 compared to indomethacin; however, it exhibits a lower affinity for COX-2 in comparison with rofecoxib. These data suggest that the steroid-oxazolone derivative could be a good candidate as COX-1 inhibitor translated as a possible drug for treatment of pain.